Harvesting & Postharvest Handling of Stonefruit in Florida - Jeffrey K. Brecht; Mark A. Ritenour; Ali Sarkhosh; Mercy Olmstead; Jose X. Chaparro; Jerry A. Bartz; Steven A. Sargent; John Van Sickle (EDIS)
Stonefruit grown commercially in Florida include peaches, nectarines, and plums. This publication is directed to current and potential stonefruit growers, handlers, and marketers, as well as researchers, extension agents, students, and consumers. It provides information about the Florida stonefruit industry, stonefruit cultivars that are suitable for Florida, stonefruit postharvest physiology and pathology, fruit quality, and recommended postharvest handling and marketing practices.